Face validity of the pulsatile organ perfusion trainer for laparoscopic cholecystectomy - Nickel, Felix; Kowalewski, Karl-Friedrich; Rehberger, Florian; Hendrie, Jonathan D.; Mayer, Benjamin; Kenngott, Hannes Götz; Linke, Georg R.; Fischer, Lars; Müller, Beat P. (Surgical endoscopy and other interventional techniques, 2017)
The pulsatile organ perfusion (POP) trainer provides training of minimally invasive surgery (MIS) with real instruments and cadaveric organs. It provides training of full procedures with simulation of bleeding. Although widely used, the face validity has not yet been evaluated. This study aimed to establish face validity of the POP trainer for laparoscopic cholecystectomy (LC) and its usefulness compared with other training modalities.